Definition and diagnosis of fracture-related infection. Issue 10 (October 2020) - McNally, Martin; Govaert, Geertje; Dudareva, Maria; Morgenstern, Mario; Metsemakers, Willem-Jan
Abstract : Fracture-related infection (FRI) is common and often diagnosed late. Accurate diagnosis is the beginning of effective treatment. Diagnosis can be difficult, particularly when there are no outward signs of infection. The new FRI definition, together with clear protocols for nuclear imaging, microbiological culture and histological analysis, should allow much better study design and a clearer understanding of infected fractures. In recent years, there has been a new focus on defining FRI and avoiding non-specific, poorly targeted treatment. Previous studies on FRI have often failed to define infection precisely and so are of limited value. This review highlights the essential principles of making the diagnosis and how clinical signs, serum tests, imaging, microbiology, molecular biology and histology all contribute to the diagnostic pathway. Cite this article: EFORT Open Rev 2020;5:614-619. DOI: 10.1302/2058-5241.5.190072